1997
DOI: 10.1159/000227695
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of bcl-2 and p53 Proteins and Apoptosis in Soft Tissue Sarcoma: Their Correlations with Prognosis

Abstract: Information on prognostic factors is essential to establish appropriate therapeutic modalities for soft tissue sarcoma (STS). To evaluate the biological nature and prognostic factors of STS, p53 and bcl-2 expression was immuno-histochemically studied on paraffin-embedded sections from 70 patients with STS in the extremities and trunk. In addition, the degree of apoptosis was examined by in situ end-labeling. Histologic diagnoses in these cases were malignant fibrous histiocytoma in 29 cases, liposarcoma in 11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 19 publications
3
46
0
1
Order By: Relevance
“…However, the great number of studies that have been performed without reaching an answer as to a prognostic role of p53 in STS indicate that a possible prognostic importance of p53 immunostaining is small. The transcription regulators Rb and Bcl-2 also interact with p53 function and it is possible that combined alterations in these pathways may be of prognostic importance [36,113,116,122,185].…”
Section: P53 Mdm2 and Bcl-2mentioning
confidence: 99%
“…However, the great number of studies that have been performed without reaching an answer as to a prognostic role of p53 in STS indicate that a possible prognostic importance of p53 immunostaining is small. The transcription regulators Rb and Bcl-2 also interact with p53 function and it is possible that combined alterations in these pathways may be of prognostic importance [36,113,116,122,185].…”
Section: P53 Mdm2 and Bcl-2mentioning
confidence: 99%
“…The bcl-2 protooncogene encodes a 26 kDa protein mainly localized in mitochondrial membranes and this bcl-2 protein has been shown to prolong cell survival by inhibiting the apoptotic processes induced by many anticancer drugs, radiation and DNA-damaging agents, processes that are mediated by p53 (Hockenbery et al, 1990;Sentman et al, 1991;Korsmeyer et al, 1992;Miyashita et al, 1993;Wang et al, 1993). bcl-2 expression has been demonstrated in a variety of human cancers (Colombel et al, 1993;Joensuu et al, 1994) and it has been reported that bcl-2 expression is of prognostic significance in a number of malignancies (Baretton et al, 1996;Nakanishi et al, 1997;Nakopoulou et al, 1998), as is the expression of p53. In some cancers, bcl-2 expression correlates with negative p53 staining (which implies the presence of wildtype p53) (Silvestrini et al, 1994;Alderson et al, 1995;Fontanini et al, 1995).…”
mentioning
confidence: 99%
“…By contrast, when p53 is mutated, its half-life becomes longer, it accumulates at nuclear level and DNA-damaged cells can continue to proliferate, resulting in tumor. Recently, Nakanishi 17 found that 27% of synovial sarcoma were p53 positive and he consiclered this data indicative of abnormal accumulation of p53. P53 presence in this tumor could be expression of nuclear damage, but this fact alone is not helpful in pathogenetic speculation.…”
Section: Discussionmentioning
confidence: 93%
“…Analogously, Nicholson 18 and Suster 25 found Bcl-2 positivity in 100% of synovial sarcomas. Segers 23 and Nakanishi 17 found that synovial sarcoma could be also Bcl-2 negative. In addition, Nakanishi 17 underlined the possibility that patients with Bcl-2 positive soft tissue tumors showed more favourable prognosis than those Bcl-2 negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation